**Solution:**

**(i)1/4, -1**

Now formula of quadratic equation is

x²-(Sum of root)x + (Product of root) = 0

Plug the value in formula we get

x² –(1/4)x -1 = 0

Multiply by 4 to remove denominator we get

4x² - x -4 = 0

**(ii) √2 , 1/3 **

Now formula of quadratic equation is

x²-(Sum of root)x + (Product of root) = 0

Plug the value in formula we get

x² –(√2)x + 1/3 = 0

Multiply by 3 to remove denominator we get

3x² - 3√2 x + 1 = 0

**(iii) 0, √5**

Now formula of quadratic equation is

x²-(Sum of root)x + (Product of root) = 0

Plug the value in formula we get

x² –(0)x + √5 = 0

simplify it we get

x² + √5 = 0

**(iv) 1,1 **

Now formula of quadratic equation is

x²-(Sum of root)x + (Product of root) = 0

Plug the value in formula we get

x² –(1)x + 1 = 0

simplify it we get

x² - x + 1 = 0

**(v) -1/4 ,1/4**

Now formula of quadratic equation is

x²-(Sum of root)x + (Product of root) = 0

Plug the value in formula we get

x² –(-1/4)x + 1/4 = 0

multiply by 4 we get

4x² + x + 1 = 0

**(vi) 4,1**

Now formula of quadratic equation is

x²-(Sum of root)x + (Product of root) = 0

Plug the value in formula we get

x² –(4)x + 1 = 0

x^{2} –4x + 1 = 0